2003
DOI: 10.1001/archneur.60.4.553
|View full text |Cite
|
Sign up to set email alerts
|

A Clustering of Conjugal Amyotrophic Lateral Sclerosis in Southeastern France

Abstract: Background:The origin of amyotrophic lateral sclerosis (ALS) remains largely unknown but seems to be multifactorial. We believe that ALS clusters may help clinicians understand or analyze the role of environmental factors in ALS pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 25 publications
0
21
1
Order By: Relevance
“…A cluster discovered in France [65] where 9 couples developed ALS between 1975 and 1992, implied a possible role of shared environmental exposure to exogenous factors or infections. Two significant population clusters were found in Finland with over a third of ALS cases, but only 24% of Finland's population, demonstrating a relation between the clusters and the place of birth (more than to the place of death).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cluster discovered in France [65] where 9 couples developed ALS between 1975 and 1992, implied a possible role of shared environmental exposure to exogenous factors or infections. Two significant population clusters were found in Finland with over a third of ALS cases, but only 24% of Finland's population, demonstrating a relation between the clusters and the place of birth (more than to the place of death).…”
Section: Discussionmentioning
confidence: 99%
“…ALS seems affecting men more frequently than women (ratio 1.4:1.0) [1,6] and the age class with higher risk is [65][66][67][68][69][70][71][72][73][74]. Prognosis is about 2-3 years from the beginning of the disease, though some 12-15 years survival cases have been observed, mainly in the older age classes [7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, this was an isolated observation and it does not permit a definite conclusion. The largest series on conjugal ALS 24 observed that the long period of conjugal life is more compatible with environmental factors, but concluded that the possibility coincidence cannot be rejected.…”
Section: Resultsmentioning
confidence: 99%
“…conjugal ALS was noted in 10 couples on Guam, where ALS was 50 to 100 times more common 15 . Since then there were other reports outside the Western Pacific [16][17][18][19][20][21][22][23][24][25] . except in Guam, where an environmental factor was considered, none of the previous reports pointed out a clear explanation for appearance of these clusters.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 Most of these appear to have dropped by the wayside in recent years. Nevertheless, reports of clear-cut clusters of patients with ALS in nonendemic areas of the world should return our attention to environmental causes of ALS 5,6 (E. W. Stommel, 2007, personal communication). We may now have some clues to at least one of the environmental factors that can cause ALS.…”
mentioning
confidence: 99%